Effects of Acute Alcohol Intake on Nasal Patency. Issue 3 (May 2022) - Deng, Yuzhoujia; Wang, Chengshuo; Shen, Shen; Yang, Xiaozhe; Lou, Hongfei; Zhang, Luo
Background: Acute alcohol intake may influence nasal patency; however, there is lack of objective evidence. Objective: The aim of this study was to evaluate the effects of acute alcohol intake on nasal patency employing both subjective and objective measures. Methods: A total of 31 participants were classified into 2 groups of non-heavy drinkers (n = 17) and heavy drinkers (n = 14). Both groups consumed wine in 1 h and were assessed for subjective nasal symptoms and objective nasal patency, using rhinomanometry and acoustic rhinometry, at baseline and at 0.5, 2, and 6 h post-alcohol consumption. Results: Alcohol consumption significantly increased nasal obstruction from baseline values in both heavy and non-heavy drinking groups. Total nasal volume (TNV) and the minimal cross-sectional area (MCA) were significantly decreased and nasal airway resistance (NAR) significantly increased from baseline values by 2 h post-alcohol consumption for both heavy and non-heavy drinking groups ( P  < .05). Significant differences were found in TNV, MCA, and NAR between baseline and post-drinking in allergic rhinitis subjects; with no significant differences in MCA and NAR in subjects without allergic rhinitis. Pulse rate (PR) and temperature (T) were elevated, and blood pressure (BP) was decreased after alcohol consumption ( P  < .05). Blood alcohol concentration (BAC) was not significantly correlated with nasal patency with regard to any subjective or objective measurement. Conclusion: Acute alcohol consumption may impair nasal patency, independent of the amount consumed. Individuals with allergic rhinitis may be more prone to nasal obstruction after alcohol consumption than those without allergic rhinitis.